2007
DOI: 10.1196/annals.1402.030
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Hypercalciuric Nephrolithiasis

Abstract: Renal stone disease (nephrolithiasis) affects 5% of adults and is often associated with hypercalciuria. Hypercalciuric nephrolithiasis is a familial disorder in more than 35% of patients, and may occur as a monogenic disorder, or as a polygenic trait involving 3 to 5 susceptibility loci in man and rat, respectively. Studies of monogenic forms of hypercalciuric nephrolithiasis in man, for example, Bartter syndrome, Dent's disease, autosomal dominant hypocalcemic hypercalciuria (ADHH), hypercalciuric nephrolithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 119 publications
(239 reference statements)
1
45
0
1
Order By: Relevance
“…Patients with idiopathic hypercalciuria (IH), defined as excessive urinary calcium without a demonstrable metabolic cause, generally have normal serum calcium, normal or elevated serum 1,25-dihydroxyvitamin D3, normal or elevated serum parathyroid hormone (PTH), normal or low serum phosphate, and low bone mass. 1,4,5 IH exhibits a polygenic mode of inheritance. [4][5][6] The annual incidence of kidney stones in industrialized nations exceeds 1 per 1000 persons, with a lifetime risk of about 7% in women and about 11% in men.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with idiopathic hypercalciuria (IH), defined as excessive urinary calcium without a demonstrable metabolic cause, generally have normal serum calcium, normal or elevated serum 1,25-dihydroxyvitamin D3, normal or elevated serum parathyroid hormone (PTH), normal or low serum phosphate, and low bone mass. 1,4,5 IH exhibits a polygenic mode of inheritance. [4][5][6] The annual incidence of kidney stones in industrialized nations exceeds 1 per 1000 persons, with a lifetime risk of about 7% in women and about 11% in men.…”
mentioning
confidence: 99%
“…1,4,5 IH exhibits a polygenic mode of inheritance. [4][5][6] The annual incidence of kidney stones in industrialized nations exceeds 1 per 1000 persons, with a lifetime risk of about 7% in women and about 11% in men. 7 After an initial episode of nephrolithiasis, approximately 60%-80% of patients form at least one recurrent stone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypercalcemia with hypercalciuria cause the occurrence of calcium nephrolithiasis, by increasing the urinary saturation of calcium salts and by binding negatively charged inhibitors of stone formation (13,14). Between 35% and 65% of hypercalciuric stome formers and up to 70% of subjects with hypercalciuria have relatives with nephrolithiasis (15,16). Calcium stones are also associated with several monogenic mendelian traits, many of which affect ion channels and membrane transporters (16).…”
Section: Discussionmentioning
confidence: 99%
“…Between 35% and 65% of hypercalciuric stome formers and up to 70% of subjects with hypercalciuria have relatives with nephrolithiasis (15,16). Calcium stones are also associated with several monogenic mendelian traits, many of which affect ion channels and membrane transporters (16). Goodman et all concluded that stone formers have a relative risk of having abnormal calciemia and calciuria 9,18 times more than do nonstone formers (17).…”
Section: Discussionmentioning
confidence: 99%